Efektivitas Konten Dakwah Tiktok dalam Meningkatkan Literasi Belajar Remaja - Wahyu Adriansyah; Umar Natuna; Eka Saputri; Murfan Franoto (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
This article analyzes the effectiveness of TikTok da'wah content in improving learning literacy among adolescents. Learning literacy is understood as the ability to access, understand, evaluate, and apply knowledge in a responsible learning process. This qualitative library study reviews 15 scholarly references published from 2021 to 2026 related to TikTok, digital da'wah, Islamic education, microlearning, media literacy, and short-video risks. The findings indicate that TikTok da'wah content can strengthen adolescents' learning literacy when it is brief, visual, authentic, interactive, and supported by credible Islamic sources. The synthesis is articulated through the ACRE framework: Access, Comprehension, Reflection, and Ethical Action. However, TikTok's algorithm, misinformation, fragmented understanding, and excessive use may reduce critical thinking and learning motivation. Therefore, TikTok da'wah requires guidance from teachers, parents, and credible religious authorities so that adolescents become critical, ethical, and spiritually responsible learners.